Considering neurophysiological mechanisms of dual-tasking in people with multiple sclerosis: an exploratory, cross-sectional small-N study - Plandowski, Kristen E.; Donkers, Sarah J.; Moslemi, Zahra; Ahmad, Maruf; Mang, Cameron S. (Frontiers in Neurology, 2026)
IntroductionDual-tasking is an emerging topic of study within the field of multiple sclerosis (MS) rehabilitation. Past research on dual-task performance among people with MS (PwMS) is limited by methodological differences and minimal consideration of underlying neurophysiology. Related studies suggest that changes in inhibitory neural activity in the motor cortex may support dual-task performance in healthy adults, as assessed using transcranial magnetic stimulation (TMS). Other TMS work indicates that MS alters corticospinal inhibition, but how and whether it is modulated during dual-tasking in PwMS is unknown. The objective of this exploratory, cross-sectional small-N study was to explore whether changes in corticospinal inhibition that occur during dual-tasking may be different in PwMS compared to non-MS controls.MethodsSix PwMS (4F; 45.17 ± 15.74 years) and three non-MS controls (2F; 42.33 ± 16.62 years) performed motor and cognitive tasks under single- and dual-task conditions. Each dual-task included a core motor task, which involved maintaining a steady pinch grip force. Performance of this core motor task allowed for assessment of corticospinal inhibition during task performance via measurement of the cortical silent period elicited by TMS. Tasks combined with the core motor task included holding a string of numbers and/or number letter combinations in working memory and a toe-tapping task. Several versions of the tasks were presented alongside the core motor task, each providing different levels of novelty and complexity. Dual-task performance was measured as dual-task cost, considering task performance and cortical silent period duration. Analyses included descriptive statistics and, in line with a small-N study design, examination of individual data.ResultsThere was no evidence of greater cognitive-motor interference in PwMS relative to non-MS controls. Task novelty and complexity effects between PwMS and non-MS controls were similar. Despite behavioral similarities, PwMS displayed greater changes in cortical silent period under dual-task conditions compared to non-MS controls that were accentuated under motor-motor dual-task conditions.DiscussionFindings suggest that while PwMS and non-MS controls may perform similarly during dual-tasking, the neurophysiological mechanisms involved may be different. Further work is needed to elucidate the impact of MS-related changes in the corticospinal system on dual-tasking.